Ester oil as an alternative to mineral transformer insulating liquid. (2021) - Srivastava, Manish; Goyal, Sunil Kumar; Saraswat, Amit
Abstract: The function of oil used in large size transformers are cooling and insulation. Transformer oil must have certain properties like high dielectric strength, low viscosity, high flash point, very low moisture or water content, high specific resistance and many more. Petroleum based synthetic and mineral oil used over last few decades, which affects the environment because of their non-biodegradability characteristics. It can be overcome by using any liquid as coolant and insulation purpose in transformer, which should have all the basic properties of transformer oil and should be biodegradable. Due to several advantages, researchers focused on biodegradable and renewable alternative of mineral oil. Ester oil has been considered as a substitute of conventional petroleum based oil. Plants of soya, sunflower and rapeseed are the sources of natural ester oil which is substitute of mineral oil. A journey of different materials used for transformer oil have been presented. Different properties of transformer oils along with the causes of failure of insulation have also been discussed. Various Ester oils have been used as an alternative to mineral oils. Different Ester oils along with their properties are also discussed.